A Meta-Analysis on Contextual Interference Effect on Motor Skills - Jiménez Díaz, Judith (2016)
The present study extend a recent meta-analysis and use the aggregate data meta-analytic approach to examine the Contextual Interference Effect (CIE). Randomized trials of block (B) group versus random (R) group skill acquisition were included by searching eleven databases, cross-referencing and expert review. 25 studies met the inclusion criteria for the within-groups analysis and 21 studies for between-groups analysis. Following a random model, for the within-group analysis, a total of 150 effect size were calculated. The B group significantly improved performance during the acquisition phase (ES = 0.69, n= 39, CI95%= 0.40 to 0.97, Q= 204.3) and significantly decreased performance during the retention phase (ES = -0.25, n=43, CI95%= -0.51 to -0.02; Q= 207.6). The R group also significantly improved performance during the acquisition phase (ES = 0.79, n=31, CI95%= 0.43 to 1.16; Q= 200.5) with no statistically significant changes during the retention phase (ES = 0.12, n=37, CI95%= -0.12 to 0.38; Q= 158). For between-group analysis, a total of 68 effect size were calculated, the B group outperformed the R group in acquisition phase (ES = -0.15, n=31, CI95%= -0.32 to -0.01; Q= 41.16) with no statistically significant between-group differences during the retention phase (ES = -0.02, n=37, CI95%= -0.20 to 0.26; Q= 124.3). The results shown support the CIE for acquisition phase and confirm that the effect is mediated by the age of the participant, the amount of trials, the type of the skill considering muscular group and precision of the movement, and external validity of the study.  The present study extend a recent meta-analysis and use the aggregate data meta-analytic approach to examine the Contextual Interference Effect (CIE). Randomized trials of block (B) group versus random (R) group skill acquisition were included by searching eleven databases, cross-referencing and expert review. 25 studies met the inclusion criteria for the within-groups analysis and 21 studies for between-groups analysis. Following a random model, for the within-group analysis, a total of 150 effect size were calculated. The B group significantly improved performance during the acquisition phase (ES = 0.69, n= 39, CI95%= 0.40 to 0.97, Q= 204.3) and significantly decreased performance during the retention phase (ES = -0.25, n=43, CI95%= -0.51 to -0.02; Q= 207.6). The R group also significantly improved performance during the acquisition phase (ES = 0.79, n=31, CI95%= 0.43 to 1.16; Q= 200.5) with no statistically significant changes during the retention phase (ES = 0.12, n=37, CI95%= -0.12 to 0.38; Q= 158). For between-group analysis, a total of 68 effect size were calculated, the B group outperformed the R group in acquisition phase (ES = -0.15, n=31, CI95%= -0.32 to -0.01; Q= 41.16) with no statistically significant between-group differences during the retention phase (ES = -0.02, n=37, CI95%= -0.20 to 0.26; Q= 124.3). The results shown support the CIE for acquisition phase and confirm that the effect is mediated by the age of the participant, the amount of trials, the type of the skill considering muscular group and precision of the movement, and external validity of the study.